Blockade of β-adrenergic signaling suppresses inflammasome and alleviates cardiac fibrosis - Dang, Shipeng (Ann Transl Med, 2020)
BACKGROUND: Heart failure (HF) is an end-stage syndrome of all structural heart diseases which accompanies the loss of myocardium and cardiac fibrosis. Although the role of inflammasome in cardiac fibrosis has recently been a point of focus, the mechanism of inflammasome activation in HF has not yet been elucidated. METHODS: In this study, we investigated the expression of inflammasome proteins in a rat thoracic aorta constriction (TAC) model and cultured cardiac fibroblasts with stimulation of norepinephrine (NE). RESULTS: Our results showed that levels of inflammasome proteins in the myocardial of TAC rats were elevated. By blocking β-adrenergic signaling in the rats, inflammasome activation was suppressed and heart function was improved. The stimulation of cultured cardiac fibroblasts with NE activated inflammasome in vitro, which was abrogated by the inhibition of the calcium channels and reactive oxygen species (ROS). The activation of inflammasome by NE promoted cardiac fibrosis, whereas the inhibition of the calcium channels, ROS, and inflammasome reduced this effect. CONCLUSIONS: The present study indicated that activation of inflammasome by β-adrenergic signaling promotes cardiac fibrosis. Therefore, modulation of inflammasome during HF might provide a novel strategy to treat this disease.